Pathways to mental health care in active military populations across the Five-Eyes nations: An integrated perspective. (February 2022) - Fikretoglu, Deniz; Sharp, Marie-Louise; Adler, Amy B.; Bélanger, Stéphanie; Benassi, Helen; Bennett, Clare; Bryant, Richard; Busuttil, Walter; Cramm, Heidi; Fear, Nicola; Greenberg, Neil; Heber, Alexandra; et al.
Abstract: Military service is associated with increased risk of mental health problems. Previous reviews have pointed to under-utilization of mental health services in military populations. Building on the most recent systematic review, our narrative, critical review takes a complementary approach and considers research across the Five-Eyes nations from the past six years to update and broaden the discussion on pathways to mental healthcare in military populations. We find that at a broad population level, there is improvement in several indicators of mental health care access, with greater gains in initial engagement, time to first treatment contact, and subjective satisfaction with care, and smaller gains in objective indicators of adequacy of care. Among individual-level barriers to care-seeking, there is progress in improving recognition of need for care and reducing stigma concerns. Among organizational-level barriers, there are advances in availability of services and cultural acceptance of care-seeking. Other barriers, such as concerns around confidentiality, career impact, and deployability persist, however, and may account for some remaining unmet need. To address these barriers, new initiatives that are more evidence-based, theoretically-driven, and culturally-sensitive, are therefore needed, and must be rigorously evaluated to ensure they bring about additional improvements in pathways to care. Highlights: There have been gains in access to mental healthcare among military personnel. Gains are greater for initial and timely engagement, smaller for markers of adequacy. Pathways to care are non-linear, with fluctuating barriers/facilitators at each step. Evidence-based, theoretically-driven interventions show promise in improving access.